Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{a}{b}=\frac{c}{d}\Leftrightarrow\frac{a}{b}+1=\frac{c}{d}+1\Leftrightarrow\frac{a+b}{b}=\frac{c+d}{d}\) (dpcm)
a) \(\frac{x-2}{5}=\frac{3}{8}\)
(x-2).8=5.3
(x-2).8=15
x-2=15:8
x-2=\(\frac{15}{8}\)
x=\(\frac{15}{8}+2\)
x=\(\frac{31}{8}\)
b)\(\frac{x-1}{x+5}=\frac{6}{7}\)
(x-1).7=(x+5).6
7x-7=6x+30
7x=6x+30+7
7x=6x+37
7x-6x=37
x=37
c)\(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2.25=6.24\)
\(x^2.25=144\)
\(x^2=144:25\)
\(x^2=\frac{144}{25}\)
\(x^2=\left(\frac{12}{5}\right)^2\)
\(x=\frac{12}{5}\)
a.
\(\frac{x-1}{x-5}=\frac{6}{7}\)
\(\left(x-1\right)\times7=6\times\left(x-5\right)\)
\(7x-7=6x-30\)
\(7x-6x=-30+7\)
\(x=-23\)
b.
\(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2=\frac{24}{25}\times6\)
\(x^2=\frac{144}{25}\)
\(x^2=\left(\pm\frac{12}{5}\right)^2\)
\(x=\pm\frac{12}{5}\)
Vậy \(x=\frac{12}{5}\) hoặc \(x=-\frac{12}{5}\)
a) \(\frac{x-1}{x+5}=\frac{6}{7}\)
\(\Rightarrow7.\left(x-1\right)=6.\left(x+5\right)\)
\(\Rightarrow7x-7=6x+30\)
\(\Rightarrow7x-6x=7+30\)
\(\Rightarrow x=37\)
b) \(\frac{x^2}{6}=\frac{24}{25}\)
\(\Rightarrow25.x^2=24.6\)
\(\Rightarrow25.x^2=144\)
\(\Rightarrow x^2=144:25\)
\(\Rightarrow x^2=\frac{144}{25}\)
\(\Rightarrow x^2=\frac{12^2}{5^2}\)
\(\Rightarrow x^2=\frac{12}{5}^2\)
\(\Rightarrow x=\pm\frac{12}{5}\)
\(c,\frac{x-2}{x-1}=\frac{x+4}{x+7}\)
\(\Leftrightarrow(x-2)(x+7)=(x+4)(x-1)\)
\(\Leftrightarrow x^2+5x-14=x^2+3x-4\)
\(\Leftrightarrow x^2+5x-14-x^2+3x=-4\)
\(\Leftrightarrow\left[x^2-x^2\right]+5x-3x-14=-4\)
\(\Leftrightarrow2x-14=-4\)
\(\Leftrightarrow2x=10\Leftrightarrow x=5\)
\(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2\cdot25=6\cdot24\)
\(x^2\cdot25=144\)
\(x^2=144:25\)
\(x=\pm\sqrt{\frac{12}{5}}\)
\(a,\frac{x-1}{x+5}=\frac{6}{7}\)
\(\Rightarrow7x-7=6x+30\)
\(\Rightarrow x=37\)
Vậy x=37
b) \(\frac{x^2}{6}=\frac{24}{25}\)
\(\Leftrightarrow x^2.25=6.24\)
\(\Leftrightarrow x^2.25=144\)
\(\Leftrightarrow x^2=\frac{144}{25}\)
\(\Leftrightarrow x=\pm\sqrt{\frac{144}{25}}=\pm\frac{12}{5}\)
Ta có: \(\frac{x^2}{6}=\frac{24}{25}\)
\(\Rightarrow x^2=24.6:25=5,76\)
\(\Rightarrow x=2,4\)
Vậy x = 2,4